Relationship Between Belly Fat and Cardiovascular Disease A Survey Based Study in Cardiology A Multi Center Study - Shahsawar, Umer Ibrahim Paracha, Iqtidar Uddin, Nowsherwan, Amajd Ali, Hussain Afridi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The Prevalence of central obesity is rising, and with it comes a higher risk of cardiovascular disease. Objectives: The goal is to determine whether or not central obesity is related to cardiovascular disease. Methodology: This research method was placed between January 05, 2021, and December 31, 2021, at the Department of Cardiology at GKMC Sawabi. The Prevalence of central obesity among 480 members of the general public was determined by measuring their waist circumferences. They also had their fasting blood sugar checked and their ability to exercise test. Results: The average age was 54.7011.2, and there were 288 females and 192 males. The female-to-male ratio was 60% to 40%. Men were less likely to have a waist circumference of 85 centimeters or more than women. Higher waist circumference was associated with lower and middle socioeconomic status in both sexes. The chances ratio for men against females varied greatly across age groups, body mass index, and socioeconomic position (as measured by family income). Compared to those of normal weight, those with central obesity were more likely to have dyslipidemia, ischemia, and atherosclerosis in a biochemical study of blood samples. Conclusion: Belly obesity is a major risk factor for cardiovascular disease. Keywords: Relationship, Obesity, Cardiovascular Disease